The Perspective Of Tuan Guru On Gendered Division Of Labor: Examining Gender Equality In Terong Tawah Village, Labuapi District, West Lombok Regency - Tayib, Muhtar (Prodi Pengembangan Masyarakat Islam Fakultas Dakwah dan Ilmu Komunikasi UIN Mataram, 2024)
Gender extends beyond the biological distinctions between men and women, encompassing the roles and responsibilities attributed to each as a product of social construction. Achieving gender equality necessitates equitable roles for men and women, particularly within the workforce. This study employs a case study design with a qualitative methodology to explore these dynamics. The findings reveal that many women engage in public-sector work to support their partners in managing household responsibilities, often within the framework of mutual agreement. This practice aligns with the perspectives of Tuan Guru and demonstrates how the division of labor contributes to fostering a resilient and self-reliant community. However, it also highlights potential challenges, such as social disparities within families stemming from reduced social interaction.